Extract of neem (Azadirachta indica) leaf exhibits bactericidal effect against multidrug resistant pathogenic bacteria of poultry. Issue 5 (6th May 2021) - Ali, Edris; Islam, Md. Sadequl; Hossen, Md. Ismail; Khatun, Mst. Minara; Islam, Md. Ariful
Abstract: The aim of the study was to determine the efficacy of neem leaf extract against multidrug resistant (MDR) pathogenic bacteria. Laboratory stock culture of Pasteurella multocida, Salmonella pullorum, Salmonella gallinarum and Escherichia coli was revived. Antibiogram profiles of these bacteria were determined by disc diffusion method. Ethanolic extract of neem leaf was prepared. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of neem leaf extract (112.5, 100, 50, 25, 12.5, 6.25 and 3.12 mg/ml) against MDR pathogenic bacteria of poultry were determined by double dilution method. The MIC and MBC of the neem leaf extract were 12.5 and 25 mg/ml, respectively for P. multocida, 50 and 100 mg/ml for S. pullorum and S. gallinarum, 100 and 112.5 mg/ml for E. coli . Neem leaf extracts exhibited bactericidal effect against MDR pathogenic bacteria of poultry. Xxxx: This study tested the in vitro antibacterial efficacy of neem ( Azadirachta indica ) leaf extract against pathogenic muldrug resistant bacteria of poultry. It showed promising results in inhibiting growth of bacteria and could be used as an alternative to antibiotic if found effective by in vivo trail.